2015
DOI: 10.1016/j.jallcom.2015.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Superior critical current density obtained in Mg11B2 low activation superconductor by using reactive amorphous 11B and optimizing sintering temperature

Abstract: . (2015). Superior critical current density obtained in Mg 11 B 2 low activation superconductor by using reactive amorphous 11 B and optimizing sintering temperature. Journal of Alloys and Compounds, Superior critical current density obtained in Mg11B2 low activation superconductor by using reactive amorphous 11B and optimizing sintering temperature AbstractThe un-doped Mg 11 B2 and Cu-doped Mg 11 B2 bulks using 11 B as a boron precursor were fabricated by solidstate reaction and sintered at different temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…suggested that the 11 B accelerated the Mg-B solid-solid reaction below 650 °C [28]. Hence, the MgO particles were mostly included in the growing MgB2 grains instead of aggregating at the boundary.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…suggested that the 11 B accelerated the Mg-B solid-solid reaction below 650 °C [28]. Hence, the MgO particles were mostly included in the growing MgB2 grains instead of aggregating at the boundary.…”
Section: Resultsmentioning
confidence: 99%
“…Combined with the distribution of Mg element, the MgO phase was believed to be dispersed homogeneously on the matrix rather than gathered in the hole, which implied good MgB 2 grain connectivity. A thermodynamic calculation has demonstrated that the MgO phase was formed prior to MgB 2 , and the study on undoped Mg 11 B 2 suggested that the 11 B accelerated the Mg-B solid-solid reaction below 650 • C [28]. Hence, the MgO particles were mostly included in the growing MgB 2 grains instead of aggregating at the boundary.…”
Section: Resultsmentioning
confidence: 99%
“…Among these materials, 10 B has been identified as prone to decomposing into Li and He gases through nuclear reactions with neutrons. To circumvent this issue, research efforts are underway to develop superconductors with 11 B substitutions [13][14][15]. The 10 B isotope exhibits a substantial neutron absorption cross-section [16], rendering materials containing boron challenging to assess using neutron scattering.…”
Section: Introductionmentioning
confidence: 99%